2022
DOI: 10.2174/1389200223666220810152633
|View full text |Cite
|
Sign up to set email alerts
|

Pain Allaying Epalrestat-Loaded Lipid Nanoformulation for the Diabetic Neuropathic Pain Interventions: Design, Development, and Animal Study

Abstract: Background: Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes mellitus. Epalrestat, an aldose reductase inhibitor, has been approved for clinical therapy for diabetic peripheral neuropathic pain. In the present study, solid lipid-based nanoparticles are used for oral administration of epalrestat (E-SLN) and evaluated against diabetic neuropathic pain in a rat model. Method: Experimental diabetes in rats was induced by a single dose of streptozotocin (STZ) administration. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Besides, RA is always related to persistent pain, which severely decreases the quality of life in RA patients. It is possible that RA patients may have peripheral neuropathic pain condition 81 , 82 , in which epalrestat has been used to alleviate neuropathic pain in diabetic patients 83 . Therefore, epalrestat combined with NAC may have potentiating effect in alleviating neuropathic pain associated with RA.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, RA is always related to persistent pain, which severely decreases the quality of life in RA patients. It is possible that RA patients may have peripheral neuropathic pain condition 81 , 82 , in which epalrestat has been used to alleviate neuropathic pain in diabetic patients 83 . Therefore, epalrestat combined with NAC may have potentiating effect in alleviating neuropathic pain associated with RA.…”
Section: Discussionmentioning
confidence: 99%
“…Epalrestat is a reversible noncompetitive inhibitor of aldose reductase and has selective inhibition on aldose reductase. Clinical studies have shown that epalrestat can inhibit the accumulation of sorbitol in red blood cells in patients with DPN and significantly improve patients’ conscious symptoms and neurological dysfunction 17 . At present, fewer generic formulations have been developed in China, so the successful implementation of this bioequivalence study will bring more treatment options for Chinese patients with diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the SLNs synthesized using the micro emulsification method had good encapsulation efficiency and were stable at acidic stomach pH, which was suitable for oral administration. Compared with epalrestat standard treatment, epalrestat with SLNs had the same efficacy, was less hepatotoxic, and could effectively improve streptozotocin-induced diabetic neuropathic pain [ 36 ].…”
Section: Single Drug-based Nanoformulations For Pain Treatmentmentioning
confidence: 99%